2017
DOI: 10.1002/jib.451
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative capacity ofKluyveromyces marxianusandSaccharomyces cerevisiaeafter oxidative stress

Abstract: Volatile compound production during alcoholic fermentation has been studied in the production of many beverages. Temperature, yeast strain, nutrients and pH have been identified as important factors in the production of volatile compounds. In addition, other factors could influence this production during the fermentation process as well. Oxidative stress could occur during yeast biomass production because oxygen is an essential nutrient that is added to the growth medium. The fermentation parameters and the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…The strong contribution of these species in the modification of the sensory profile of tchapalo is not surprising since several authors have reported that these yeasts can produce metabolites capable of having an impact on the aromatic profile of alcoholic beverages (Magyar and Toth 2011; Arellano‐Plaza et al . 2017). For tchapalo inoculated with AAB strains (G4), only the taste was noted as spoiled (80% of the panellists) with A. cerevisiae whereas with A. pasteurianus the taste and odour were spoiled.…”
Section: Resultsmentioning
confidence: 99%
“…The strong contribution of these species in the modification of the sensory profile of tchapalo is not surprising since several authors have reported that these yeasts can produce metabolites capable of having an impact on the aromatic profile of alcoholic beverages (Magyar and Toth 2011; Arellano‐Plaza et al . 2017). For tchapalo inoculated with AAB strains (G4), only the taste was noted as spoiled (80% of the panellists) with A. cerevisiae whereas with A. pasteurianus the taste and odour were spoiled.…”
Section: Resultsmentioning
confidence: 99%
“…High temperature and H 2 O 2 induced oxidative stress in K. marxianus (Arellano-Plaza et al, 2017;Fu et al, 2019). Increased…”
Section: K Marxianus Cells Exhibited An Increased τ-Mean Of Nad(p)h U...mentioning
confidence: 99%
“…It is possible to activate the antioxidant system by adding non‐lethal concentrations of stressors such as H 2 O 2 for short periods, before the application of the biocontrol yeast Y. lipolytica , allowing the antioxidant system to be activated, increasing its cell viability (Liu et al., 2011). Even adding stressful compounds to K. marxianus before fermentation not only increases their antioxidant processes, but also activates the production of important volatile compounds in the production of fermented beverages (Arellano‐Plaza et al., 2017). It has been observed that non‐ Saccharomyces yeasts may have a higher resistance to oxidative stress, such as K. marxianus , which has a different respiratory capacity than S. cerevisiae , showing greater long‐term viability (Arellano‐Plaza et al., 2013).…”
Section: Stress During the Conservation Process Of Yeastsmentioning
confidence: 99%
“…Yeasts response to oxidative stress S. cerevisiae response to oxidative stress has been studied under different environments, including growth conditions, physiological conditions in which endogenous metabolism and its transitions cause harmful changes in the redox state (Gibson et al, 2008), and the addition of oxidizing compounds such as H 2 O 2 and menadione (Arellano-Plaza et al, 2017). During oxidative stress in S. cerevisiae, general transcriptional factors such as Msn2p/Msn4p, Yap1p, and Skn7p are activated, which help reprogramming gene expression in response to oxidative injury.…”
Section: 2mentioning
confidence: 99%